2006
DOI: 10.1051/0004-6361:20066244
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of TeV gamma-ray emission from the nearby starburst galaxy NGC 253

Abstract: Aims. The CANGAROO-II telescope observed sub-TeV gamma-ray emission from the nearby starburst galaxy NGC 253. The emission region was extended with a radial size of 0.3-0.6 degree. On the contrary, HESS could not confirm this emission and gave upper limits at the level of the CANGAROO-II flux. In order to resolve this discrepancy, we analyzed new observational results for NGC 253 by CANGAROO-III and also assessed the results by CANGAROO-II. Methods. Observation was made with three telescopes of the CANGAROO-II… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…GeV and TeV gamma-rays have recently been detected in nearby starburst galaxies NGC 253 (Acero et al 2009), M 82, and Large Magellanic Cloud (LMC), by Fermi-LAT (Abdo et al 2010a), High Energy Stereoscopic System (H.E.S.S.) (Itoh et al 2007) and VERI-TAS (Karlsson & for the VERITAS collaboration 2009), support the starburst galaxies as a rich source of high energy gamma-rays. If a transient starburst did occur in the GC of our Milky Way, and produced a large population of CRs responsible for the observed Fermi bubbles, and WMAP haze, what triggered and terminated the starburst phase is unclear.…”
Section: Cosmic Rays From a Starburstmentioning
confidence: 94%
“…GeV and TeV gamma-rays have recently been detected in nearby starburst galaxies NGC 253 (Acero et al 2009), M 82, and Large Magellanic Cloud (LMC), by Fermi-LAT (Abdo et al 2010a), High Energy Stereoscopic System (H.E.S.S.) (Itoh et al 2007) and VERI-TAS (Karlsson & for the VERITAS collaboration 2009), support the starburst galaxies as a rich source of high energy gamma-rays. If a transient starburst did occur in the GC of our Milky Way, and produced a large population of CRs responsible for the observed Fermi bubbles, and WMAP haze, what triggered and terminated the starburst phase is unclear.…”
Section: Cosmic Rays From a Starburstmentioning
confidence: 94%
“…Amongst the best candidates are NGC 253 (Domingo-Santamaría & Torres 2005) and M 82 (Persic, Rephaeli & Arieli 2008); in fact, NGC 253 was claimed as a TeV emitter by the CANGAROO collaboration (Itoh et al 2003), but this detection was not confirmed by later, more sensitive, observations with H.E.S.S. and CAN-GAROO (Itoh et al 2007). Bounds on emission from the ultralumious infrared galaxy Arp 220 have been reported by the MAGIC collaboration (Albert et al 2007b).…”
Section: Other Extragalactic Source Classesmentioning
confidence: 99%
“…Although γ -ray emission from M82 and NGC 253 has been sought for several years with no success (at GeV, Cillis et al 2005; and at TeV, Aharonian et al 2005, Itoh et al 2007), the launch of Fermi and the advent of powerful very high energy (VHE) γ -ray telescopes has led to recent detections of both starbursts at GeV energies (with Fermi; Abdo et al 2010a) and in VHE γ -rays (M82 with VERITAS, Acciari et al 2009; NGC 253 with HESS, Acero et al 2009). These GeV and TeV detections constrain the CR population in these dense star-forming environments.…”
Section: Introductionmentioning
confidence: 99%